The causes and effect of delay to handover the project in construction industry - Nur Fatihah, Zakeri (2015)
This thesis is to identify the main cause of project delay and to know the effects that will be happen if the project was delay in construction industry at Kelantan. It is because construction industry is important to Malaysia and it is one of the catalysts to the economic growth in Malaysia. Other than that, this thesis also can help to improve the construction industry in Kelantan. This study also provides a lot of useful input and information to those involved in the construction industry both directly and indirectly. A survey was conducted to get the data and information about the causes and effects of project delay. The survey was conducted in construction industry at Kelantan. There are 73 respondents that involve in the survey.